The dynamics of Long-Acting Reversible Contraception (LARC) choices in rural Jambi: Socio-economic perspectives - Hardiani, Hardiani; Junaidi, Junaidi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
High population growth without concurrent improvements in human quality poses significant challenges in promoting equitable welfare across various life aspects. Thus, population control is crucial for achieving sustainable development goals. This study emphasizes the role of Long-Acting Reversible Contraception (LARC) in managing fertility rates and investigates three main components of population growth: fertility, mortality, and migration. The objectives are threefold: 1) Analyze the profile of fertile-age couples using LARC in rural Jambi; 2) Investigate the socio-economic factors influencing the choice between LARC and non-LARC methods among these couples; 3) Explore the relationship between the couples' characteristics and their choice of LARC. Data were collected from a survey of 200 fertile-age couples participating in a family planning program across four villages in Jambi. The analysis utilized descriptive statistics, binary logistic regression, and multinomial logistic regression. Findings indicate that LARC usage among fertile-age couples in rural Jambi is low, at approximately 28% of total contraceptive users, with implants being the most common LARC type. In contrast, non-LARC methods are more prevalent, accounting for 72% of usage, dominated by three-month injectables, followed by pills and male condoms. Significant factors influencing the choice between LARC and non-LARC include the husband's education, the woman's employment status, the number of living children, the disparity between actual and ideal family size, desire for more children, knowledge about contraceptive options, and family income. Furthermore, characteristics significantly related to the choice of LARC methods such as tubal ligation, implants, and IUDs include the woman's age, number of living children, the gap between the ideal and actual number of children, desire for more children, woman's employment status, knowledge about contraceptive devices, and family income.